Neither Postabsorptive Resting Nor Postprandial Fat Oxidation Are Related to Peak Fat Oxidation in Men With Chronic Paraplegia - Jacobs, Kevin A.; McMillan, David W.; Maher, Jennifer L.; Bilzon, James L. J.; Nash, Mark S. (Frontiers in Nutrition, 2021)
The peak rate of fat oxidation (PFO) achieved during a graded exercise test is an important indicator of metabolic health. In healthy individuals, there is a significant positive association between PFO and total daily fat oxidation (FO). However, conditions resulting in metabolic dysfunction may cause a disconnect between PFO and non-exercise FO. Ten adult men with chronic thoracic spinal cord injury (SCI) completed a graded arm exercise test. On a separate day following an overnight fast (≥ 10 h), they rested for 60 min before ingesting a liquid mixed meal (600 kcal; 35% fat, 50% carbohydrate, 15% protein). Expired gases were collected and indirect calorimetry data used to determine FO at rest, before and after feeding, and during the graded exercise test. Participants had “good” cardiorespiratory fitness (VO2peak: 19.2 ± 5.2 ml/kg/min) based on normative reference values for SCI. There was a strong positive correlation between PFO (0.30 ± 0.08 g/min) and VO2peak (r = 0.86, p = 0.002). Additionally, postabsorptive FO at rest was significantly and positively correlated with postprandial peak FO (r = 0.77, p = 0.01). However, PFO was not significantly associated with postabsorptive FO at rest (0.08 ± 0.02 g/min; p = 0.97), postprandial peak FO (0.10 ± 0.03 g/min; p = 0.43), or incremental area under the curve postprandial FO (p = 0.22). It may be advantageous to assess both postabsorptive FO at rest and PFO in those with SCI to gain a more complete picture of their metabolic flexibility and long-term metabolic health.